Shell-crosslinked nanostructures from amphiphilic AB and ABA block copolymers of styrene-alt-(maleic anhydride) and styrene: polymerization, assembly and stabilization in one pot - Harrisson, S; Wooley, KL (Chemical communications (Cambridge, England), 2005)
Shell-crosslinked nanostructures having unusual rosette morphologies have been produced by a simple process from styrene and maleic anhydride.Shell-crosslinked nanostructures having unusual rosette morphologies have been produced by a simple process from styrene and maleic anhydride.